Engagement in primary health care among marginalized people who use drugs in Ottawa, Canada - Claire E. Kendall; Lisa M. Boucher; Jessy Donelle; Alana Martin; Zack Marshall; Rob Boyd; Pam Oickle; Nicola Diliso; Dave Pineau; Brad Renaud; Sean LeBlanc; Mark Tyndall; et al. (BMC, 2020)
Abstract Background There may be less primary health care engagement among people who use drugs (PWUD) than among the general population, even though the former have greater comorbidity and more frequent use of emergency department care. We investigated factors associated with primary care engagement among PWUD. Methods The Participatory Research in Ottawa: Understanding Drugs (PROUD) cohort study meaningfully engaged and trained people with lived experience to recruit and survey marginalized PWUD between March-December 2013. We linked this survey data to provincial-level administrative databases held at ICES. We categorized engagement in primary care over the 2 years prior to survey completion as: not engaged (< 3 outpatient visits to the same family physician) versus engaged in care (3+ visits to the same family physician). We used multivariable logistic regression to determine factors associated with engagement in primary care. Results Characteristics of 663 participants included a median age of 43 years, 76% men, and 67% living in the two lowest income quintile neighborhoods. Despite high comorbidity and a median of 4 (interquartile range 0-10) primary care visits in the year prior to survey completion, only 372 (56.1%) were engaged in primary care. Engagement was most strongly associated with the following factors: receiving provincial benefits, including disability payments (adjusted odds ratio [AOR] 4.14 (95% confidence interval [CI] 2.30 to 7.43)) or income assistance (AOR 3.69 (95% CI 2.00 to 6.81)), having ever taken methadone (AOR 3.82 (95% CI 2.28 to 6.41)), mental health comorbidity (AOR 3.43 (95% CI 2.19 to 5.38)), and having stable housing (AOR 2.09 (95% CI 1.29 to 3.38)). Conclusions Despite high comorbidity, engagement in primary care among PWUD was low. Our findings suggest that social care (housing, disability, and income support) and mental health care are associated with improved primary care continuity; integration of these care systems with primary care and opioid substitution therapy may lessen the significant morbidity and acute care use among PWUD.